Gender differences in financial literacy among college students - Falahati, Leila; Paim, Laily (Marsland Press, 2011)
The paper aims to examine gender differences in financial literacy among college students. Using the stratified sampling method, 2,340 college students from six public and five private colleges were studied. The findings indicate gender differences in different dimensions of financial literacy, in which males were more knowledgeable in financial matters than female students. The results revealed that among the six dimensions of financial literacy, male students have more knowledge concerning credit and risk management, while females are more knowledgeable in respect of general financial literacy.